Acute appendicitis in a patient immunised with COVID‐19 vaccine: A case report with morphological analysis. Issue 2 (7th June 2022) - Marconi, Ettore; Crescioli, Giada; Bonaiuti, Roberto; Pugliese, Lavinia; Santi, Raffaella; Nesi, Gabriella; Cerbai, Elisabetta; Vannacci, Alfredo; Lombardi, Niccolò
Abstract : Although the benefit/risk profile for mRNA COVID‐19 vaccines is recognised as extremely favourable, appendicitis is currently considered an adverse event (AE) of special interest. We describe the case of a 58‐year‐old female who presented with signs and symptoms of appendicitis approximately 48 hours after her first injection of the Pfizer‐BioNTech vaccine. Abdominal ultrasound revealed fluid collection in the right iliac fossa and cecal wall thickening. Following the surgical visit, CT scan with contrast showed a distended appendix with thickened walls, suggestive of acute appendicitis. The patient tested negative to upper respiratory COVID‐19 reverse transcription‐polymerase chain reaction. Clinical trials and observational studies suggest a possible association between appendicitis and COVID‐19 vaccines. Th‐1 driven granulomatous inflammation reported in our case represents an infrequent nonspecific chronic inflammation of the appendix, especially in the setting of delayed or interval appendectomy. In view of the current paediatric vaccination campaign, we recommend monitoring the safety profile and potential gastrointestinal AEs associated with mRNA COVID‐19 vaccines to swiftly manage subjects with gastrointestinal symptoms and prevent potential complications.